The gut microbiome in autoimmune diseases - de Oliveira, Gislane Lellis Vilela [UNESP] (Elsevier, 2019)
Dysbiosis observed in autoimmune diseases is associated with decreased bacteria function and diversity, impaired epithelial barrier, bacterial translocation, inflammation, and decreased regulatory T cells (Tregs) in the gut mucosa. The hypotheses proposed to link dysbiosis with autoimmune diseases include molecular mimicry, bystander T cell activation, perpetuation of autoimmunity by inflammatory milieu, T helper 17/Tregs imbalance, and the posttranslational modification of luminal proteins (PTMP) induced by enzymes from dysbiotic microbiota, which modify substrates in a different way than under eubiotic conditions. The defective PTMP might generate neoepitopes that become immunogenic and induce systemic autoimmunity and trigger autoimmune diseases. Furthermore, the gut microbiota and their metabolites could regulate immune cells and cytokine release via epigenetic modifications, suggesting their possible role in autoimmune disease development. In this chapter we clarify the role of the gut microbiota in autoimmunity and elucidate the proposed new therapeutic approaches to treat autoimmune diseases.
Keywords: Autoimmunity; Barrier disruption; Dysbiosis; Gut microbiome; Inflammation; Multiple sclerosis; Probiotics; Rheumatoid arthritis; Systemic lupus erythematosus; Type 1 diabetes